English medium instruction (EMI) in Moroccan secondary schools: Science teachers’ perception - Hammou , Salah Ben; Kesbi, Abdelaziz (Studies in Second Language Learning and Teaching, 2023)
The present study explored a small-scale English medium instruction (EMI) initiative in Moroccan secondary schools, which is part of a top-down multilingual policy based on teaching science subjects through foreign languages, namely French, English, and Spanish. 18 secondary EMI teachers of math, physics and life and earth sciences were interviewed in order to understand the new policy. Following grounded theory (GT) methodology, the findings show positive attitudes towards the implementation of EMI in Moroccan education, but the teachers seemed unsatisfied with the way it has been implemented. They thought science teachers were not prepared for such a new tendency. The study also revealed that teachers’ low English proficiency was considered the major challenge to the successful implementation of EMI in Moroccan secondary schools and the essential reason behind using the first language in the EMI classroom. To prepare future generations for extending EMI in the Moroccan education, the teachers called for a switch to English as the first foreign language, instead of French, in all levels of schooling, and suggested gradual introduction of EMI in primary and middle schools. The study ends with some implications for overcoming the challenges of the new policy.